Modelling and synthesis using response surface methodology: a comparative study. (15th December 2009) - Gadallah, Mohamed H.
Two response surface models (RSM) are developed and compared with real experimental results for the flat end milling process. These two models are UL100 and UL136. Four optimisation formulations are developed within Matlab optimisation environment. Results indicate the capability of RSM to model non-linear processes with high accuracy relative to experimental results. The optimum solutions can serve as good operating conditions for the process under study. Past studies in areas of response surface modelling and optimisation are surveyed and important conclusions are summarised.